(untitled) (Teacher Half-Yearly Journal, 2025)
Research on labor migration has recognized that parental migration has dual impacts on their children’s education. This study tries to investigate the implication of parental death on their child’s well-being in Kathmandu Valley. The objective of this article is to explore the effects of the death of parents in foreign labor migrations on the educational implications of children left behind. This cross-sectional study has followed a mixed method (quantitative and qualitative). It used a purposive sample of Kathmandu Valley and schools, respondents were selected using simple random sampling. Out of 83 students, 56 were selected aged 10-18 for the interview for this research. A semi-structured questionnaire was used to collect the information, and has collected through face-to-face interview methods. Data were processed using the SPSS 20th version and analyzed in descriptive and analytical forms. Parents’ migration positively impacts their children’s education, but the sudden death of parents negatively affects their school education. Parental death also negatively impacts the household economy and finally affects children’s school enrollment, attendance, and educational activities and achievements. About 75 percent of respondents stated that the death of parents increases financial burden and one in ten students wants to drop out of school. Poor attendance and academic outcomes are major causes of school dropouts. To address this, the government should raise and continue scholarship programs to secure schooling for children left behind.